Gender Differences in Dysfunctional Attitudes in Major Depressive Disorder - Qin, Xuemei; Sun, Jinrong; Wang, Mi; Lu, Xiaowen; Dong, Qiangli; Zhang, Liang; Liu, Jin; Ju, Yumeng; Wan, Ping; Guo, Hua; Zhao, Futao; Zhang, Yan; et al. (Frontiers in Psychiatry, 2020)
Background: Dysfunctional attitudes play a key role in the development and prognosis of depression. Gender also plays an important role in many clinical features of MDD. This study is aimed at investigating the gender differences in dysfunctional attitudes in patients with major depressive disorder (MDD). Methods: One hundred and seventy-two patients with MDD and 159 healthy controls (HCs) were enrolled in this study. Dysfunctional attitudes were assessed by the Chinese version of the dysfunctional attitude scale - form A (C-DAS-A) and depression severity was assessed by the 24-item Hamilton rating scale for depression (HAMD24). The 14-item Hamilton Anxiety Rating Scale (HAMA14) was used to measure anxiety. Factorial analysis of variance (ANOVA) of gender and diagnosis on C-DAS-A total and factor scores was adopted with age, education, and BMI controlled. Multiple linear regression analyses of DAS were performed in the MDD group. Results: First, the C-DAS-A score in the MDD group was increased significantly than HCs. Second, female patients with MDD showed significantly higher scores in C-DAS-A total and three-factor scores (seeking applause, dependence, and self-determination attitude), while no significant difference between female HCs and male HCs was detected. Third, five variables (age, gender, smoking history, HAMD24, and HAMA14) had predictive effects on and gender showed the greatest contributions to C-DAS-A total and three-factor scores (seeking applause, dependence, and self-determination attitude). Conclusion: Females with MDD may be linked to more severe cognitive distortion than their male counterparts in seeking applause, dependence, and self-determination attitude, supporting the reasonableness for gender-specific psychosocial interventions.